2018
DOI: 10.1007/s10840-018-0317-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing left ventricular mechanical and electrical activation in patients with normal and impaired systolic function using a non-fluoroscopic cardiovascular navigation system

Abstract: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01629160.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Similarly, the efficiency of our image integration method increased with each additional animal completed but remains to be improved; as a comparison, Brooks et al ( 17 ) reported a significant decrease of the fusion time in electrophysiology cases after only 15 patients. Upon availability of novel tools, dedicated devices, and capitalizing on past experiences in cardiovascular navigation ( 18 , 19 , 20 ), the operator’s experience can only improve. In addition to tool guidance, the navigation systems allow the integration of preprocedural data from noninvasive imaging modalities, which can be linked with periprocedural data acquired by the system.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the efficiency of our image integration method increased with each additional animal completed but remains to be improved; as a comparison, Brooks et al ( 17 ) reported a significant decrease of the fusion time in electrophysiology cases after only 15 patients. Upon availability of novel tools, dedicated devices, and capitalizing on past experiences in cardiovascular navigation ( 18 , 19 , 20 ), the operator’s experience can only improve. In addition to tool guidance, the navigation systems allow the integration of preprocedural data from noninvasive imaging modalities, which can be linked with periprocedural data acquired by the system.…”
Section: Discussionmentioning
confidence: 99%